2018
DOI: 10.1176/appi.ps.201700426
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Volume and Quality of Mental Health Care Among Patients With Unipolar Depression

Abstract: Admission to very-high-volume psychiatric hospital wards was associated with a greater chance of receiving guideline-recommended process performance measures for care of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 17 publications
0
19
2
2
Order By: Relevance
“…Interestingly, this study also found IPFs in the lowest tercile of Medicare psychiatric discharges to have the lowest readmission rates. The positive relationship between volume and outcomes has long been well recognized in many facets of medical care, including psychiatry (51)(52)(53)(54). However, this relationship has not consistently been found for readmissions (32), potentially because greater volume means less time spent with each patient or shorter lengths of stay (32).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this study also found IPFs in the lowest tercile of Medicare psychiatric discharges to have the lowest readmission rates. The positive relationship between volume and outcomes has long been well recognized in many facets of medical care, including psychiatry (51)(52)(53)(54). However, this relationship has not consistently been found for readmissions (32), potentially because greater volume means less time spent with each patient or shorter lengths of stay (32).…”
Section: Discussionmentioning
confidence: 99%
“…Personen mit der Diagnose Schizophrenie, Schizophrenie und Diabetes oder Depression auf einer Station behandelt wurden, desto größer war die Wahrscheinlichkeit, dass sie eine leitliniengerechte Behandlung erhielten [15][16][17].…”
Section: Dies Wird Auch Von Dänischen Registerstudien Zur Behandlung ...unclassified
“…Study II (93) and study III ( 94) comprised all inpatients (18 years old) from the Danish Depression Database with an admission between 1 January 2011 and 31 December 2017. To ensure that only patients with incident depression were included, patients with a registration of a depressive diagnosis in the Danish National Patient Registry up to ten years before their first registration in the Danish Depression Database and all non-incident admissions were excluded.…”
Section: Study II + Iiimentioning
confidence: 99%
“…In the second study inpatient volume was defined as the average annual number of patients with a depressive disorder treated at a psychiatric hospital from January 1, 2011, and December 31, 2016. Inpatient volume was divided into tertiles and defined as low volume (< 267 patients per year), medium volume (268-477 patients per year) and high volume (> 478 patients per year) (93).…”
Section: Study II + Study Iiimentioning
confidence: 99%
See 1 more Smart Citation